Investigation of brightness and decay characteristics of YAG:Ce3+, Ca-α-Sialon:Eu2+ and CaAl12O19:Mn4+ phosphors incorporated with Ni-doped SnO2 particles - Zeyrek Ongun, Merve (Journal of luminescence, 2021)
In this study, we investigated the enhancement in the optical and decay properties of three phosphors, Ce3+-doped yttrium aluminium garnet (YAG:Ce3+), Eu2+-doped yellow oxynitride phosphor (Ca-α-SiAlON:Eu2+), Mn4+-doped aluminate-based phosphor (CaAl12O19:Mn4+), as a result of the interactions of the light-harvesting Ni-doped SnO2 additive. When the YAG:Ce3+ encapsulated in the presence of the nanoscale metal oxide in ethyl cellulose (EC) thin film, exhibited a 59% increase in its brightness as against its non-additive form. Similarly, when excited by 466 nm, the individual blends of Ca-α-SiAlON:Eu2+ and CaAl12O19:Mn4+ phosphors with Ni-doped SnO2 particles demonstrated 65% and 93% improvement in the intensity values, respectively. Decay characteristics of the phosphors and their Ni-doped SnO2 blends were measured in microsecond and nanosecond time scales. When they are in close proximity in a polymeric matrix, the emission- and lifetime-based results have approved that Ni-doped SnO2 particles and phosphors act as donor and acceptor, respectively. Furthermore, the thermal stabilities, quantum efficiencies and CIE chromaticity coordinates of all phosphors and their blends with Ni-doped SnO2 additive were investigated. In parallel with the increase in emission-based intensities and decay time kinetics, we enhanced the internal quantum efficiencies to 94.1%, 86.2% and 80.4%, with the blending of Ni-doped SnO2 particles to YAG:Ce3+, Ca-α-SiAlON:Eu2+, and CaAl12O19:Mn4+ phosphors, respectively. Notably, all of the phosphor composites along with additive indicated higher thermal stability in the temperature range of 303–503 K with respect to the additive-free forms. In the light of these results, the proposed composites can bring a new approach for the existing problems of yellow, orange, and red phosphors concerning the brightness and color rendering index and can be considered as potential candidates on LED technologies. •YAG:Ce3+, Ca-α-Sialon:Eu2+ and CaAl12O19:Mn4+ along with Ni-doped SnO2 showed 2.4-, 3- and 13-fold enhancement of brightness.•The phosphors blends with Ni-doped SnO2 exhibited high quantum efficiency, excellent thermal stability and color purity.•Enhanced brightness of proposed materials may bring new approach for fabricating more efficient phosphors in a low-cost way.